1964
DOI: 10.1111/j.1151-2916.1964.tb14417.x
|View full text |Cite
|
Sign up to set email alerts
|

Creep, Strength, Expansion, and Elastic Moduli of Sintered BeO As a Function of Grain Size, Porosity, and Grain Orientation

Abstract: Physical properties are presented for extruded and sintered B e 0 from 25" to 1400°C as a function of porosity (0 to 15%), grain size (5 to loop), and grain orientation (random to 80% preferred). T h e elastic constants and linear thermal expansion are sensitive to the degree of preferred grain orientation. Measurements on polycrystalline specimens permitted calculation of the anisotropy in single crystals of B e 0 for these properties. Modulus of rupture data are treated in terms of the Knudsen equation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(28 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Hot pressing of BeO typically results in higher densification for a given final grain size than pressureless sintering, and this results in higher strength. For pressureless sintering, an optimal compromise between densification and grain size is typically found in the grain size range 5-20 µm, with relative density ≥ 95% [49,59]. Even still, the typical flexural strength of BeO is lower than that of the other ceramics considered in this study, with some RT values as low as 100-150 MPa reported [49,52].…”
Section: Flexural Strengthmentioning
confidence: 79%
See 4 more Smart Citations
“…Hot pressing of BeO typically results in higher densification for a given final grain size than pressureless sintering, and this results in higher strength. For pressureless sintering, an optimal compromise between densification and grain size is typically found in the grain size range 5-20 µm, with relative density ≥ 95% [49,59]. Even still, the typical flexural strength of BeO is lower than that of the other ceramics considered in this study, with some RT values as low as 100-150 MPa reported [49,52].…”
Section: Flexural Strengthmentioning
confidence: 79%
“…The strength of BeO typically increases above room temperature, reaching a strength maximum between 500-1200°C, and then decreases rapidly at higher temperatures [54,57,59,150]. However, the maxima are not always observed.…”
Section: Flexural Strengthmentioning
confidence: 99%
See 3 more Smart Citations